2014
DOI: 10.1617/s11527-014-0518-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of corrosion on the bond strength of steel rebars in concrete

Abstract: The problem of the durability of reinforced concrete structures is arisen, dramatically, in the last decades, showing that one of the most dangerous degradation phenomena is connected to the rebars corrosion. When active corrosion grows the oxides occupy a volume of about 2–4 times, with respect to the sound bar, causing a loss of bond, cracking and cover spalling. In this paper the corrosion effects at the steel–concrete interface are analysed. At this aim, pull-out tests are carried out, with different corro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 164 publications
(64 citation statements)
references
References 25 publications
0
55
0
Order By: Relevance
“…The main difference of the proposed procedure, with respect to the above cited ones, lies in the possibility of recognizing, through a physical, analytical model, the actual failure mode (splitting of the concrete cover or pull-out of the ribbed bar), accounting for the stirrup presence. In particular, the proposed model extends the studies by Tepfers (1979) and den Uijl and Bigaj (1996), developed for unconfined elements on a thick-walled cylinder and by Coccia et al (2014) for the evaluation of the corrosion in reinforced concrete elements on the bond strength, introducing the effect of transverse reinforcement. Finally, a formulation of the bond-slip relationship, expressed as a function of the mechanical and geometrical parameters, is obtained through a regression with the ordinary least squares method, based on the analytical outcomes of a parametric survey.…”
Section: Introductionmentioning
confidence: 52%
“…The main difference of the proposed procedure, with respect to the above cited ones, lies in the possibility of recognizing, through a physical, analytical model, the actual failure mode (splitting of the concrete cover or pull-out of the ribbed bar), accounting for the stirrup presence. In particular, the proposed model extends the studies by Tepfers (1979) and den Uijl and Bigaj (1996), developed for unconfined elements on a thick-walled cylinder and by Coccia et al (2014) for the evaluation of the corrosion in reinforced concrete elements on the bond strength, introducing the effect of transverse reinforcement. Finally, a formulation of the bond-slip relationship, expressed as a function of the mechanical and geometrical parameters, is obtained through a regression with the ordinary least squares method, based on the analytical outcomes of a parametric survey.…”
Section: Introductionmentioning
confidence: 52%
“…Subsequent studies performed by Zhang [40] on the same beams have shown that the corrosion morphology change (from a pitting corrosion to a generalized corrosion) with the cracking propagation. After 26 years Khan [41] finds that the Rodriquez's formulation accurately predicts the crack width only if the attack penetration parameter is fixed equal to 8, while the Vidal et al model appears in a quite good agreement with the experimental results.…”
Section: (13)mentioning
confidence: 97%
“…As it was shown in [13][14][15][16][17][18][19] in the practical evaluation, one finds that the influence of the most basic variables is not as important as predicted. For instance, one originally regards that the deflection and strength of each member will result in decreased safety in the existing structure.…”
Section: Figure 1 -Block Diagram Of the Fuzzy Logic System [8]mentioning
confidence: 99%